The neck region of the myosin motor domain acts as a lever arm to generate movement. - Uyeda, T Q (1996)
The myosin head consists of a globular catalytic domain that binds actin and hydrolyzes ATP and a neck domain that consists of essential and regulatory light chains bound to a long alpha-helical portion of the heavy chain. The swinging neck-level model assumes that a swinging motion of the neck relative to the catalytic domain is the origin of movement. This model predicts that the step size, and consequently the sliding velocity, are linearly related to the length of the neck. We have tested this point by characterizing a series of mutant Dictyostelium myosins that have different neck lengths. The 2xELCBS mutant has an extra binding site for essential light chain. The delta RLCBS mutant myosin has an internal deletion that removes the regulatory light chain binding site. The delta BLCBS mutant lacks both light chain binding sites. Wild-type myosin and these mutant myosins were subjected to the sliding filament in vitro motility assay. As expected, mutants with shorter necks move slower than wild-type myosin in vitro. Most significantly, a mutant with a longer neck moves faster than the wild type, and the sliding velocities of these myosins are linearly related to the neck length, as predicted by the swinging neck-lever model. A simple extrapolation to zero speed predicts that the fulcrum point is in the vicinity of the SH1-SH2 region in the catalytic domain.